Tinjauan Literatur Sistematis dan Kajian Bibliometrik Peran Stakholder dalam Perkembangan Pariwisata Menggunakan Analisis Jaringan Sosial - Redha Maulana Yusra; Hidayatul Fajri (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This study aims to determine the role of stakeholders in tourism management using social network analysis. The research was carried out through systematic literature reviews and bibliometric studies, to identify trends and patterns in research related to tourism management by involving stakeholders. This research was conducted from 06/May/2023 to 06/April/2023. To describe the issues mentioned above about the role of stakeholders in the development of Tourism Using Social Network Analysis. It therefore extracts data from Google Scholar as the leading indexing service for peer-reviewed publications. Of the more than 94 titles on Google Schooler using the Publish of Perish application related to the keywords